Measurements of the liquid-liquid coexistence curves of (1 − x) dimethyl carbonate + x pentadecane and (1 − x) dimethyl carbonate + x heptadecane in the critical region. (January 2019) - Guo, Yimin; Shi, Aiqin; Chen, Zhiyun; Shen, Weiguo
Highlights: Liquid-liquid coexistences of binary solutions of dimethyl carbonate + n -alkane were measured. Critical exponents were obtained and found to be in agreement with the 3-D Ising universality. Asymmetry of the coexistence curves were analyzed by the complete scaling theory. Chain-length dependences of the critical parameters were discussed. Abstract: The liquid-liquid coexistence curves in a temperature range of about 10 K from the upper consolute critical temperature for binary solutions of dimethyl carbonate + pentadecane and dimethyl carbonate + heptadecane have been precisely measured. The upper consolute mole fraction x c of n -alkane and the upper consolute temperature T c were determined to be x c = 0.210, T c = 312.234 K for dimethyl carbonate + pentadecane and x c = 0.183, T c = 320.496 K for dimethyl carbonate + heptadecane, respectively. From the data collected in the near critical point, the critical exponent β was deduced and shown to be consistent well with its theoretical value for the 3-D Ising universality class. The dependences of critical properties on the chain length of n -alkane for a series of dimethyl carbonate + n -alkane binary solutions were investigated. Furthermore, it was found that the asymmetric behaviors of the coexistence curve could be well described by the complete scaling theory. The contribution of the heat capacity related term to the asymmetric behaviors of the coexistence curves was discussed.